3ax-2m-7ax=-5ax-12m

Simple and best practice solution for 3ax-2m-7ax=-5ax-12m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ax-2m-7ax=-5ax-12m equation:


Simplifying
3ax + -2m + -7ax = -5ax + -12m

Reorder the terms:
3ax + -7ax + -2m = -5ax + -12m

Combine like terms: 3ax + -7ax = -4ax
-4ax + -2m = -5ax + -12m

Solving
-4ax + -2m = -5ax + -12m

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5ax' to each side of the equation.
-4ax + 5ax + -2m = -5ax + 5ax + -12m

Combine like terms: -4ax + 5ax = 1ax
1ax + -2m = -5ax + 5ax + -12m

Combine like terms: -5ax + 5ax = 0
1ax + -2m = 0 + -12m
1ax + -2m = -12m

Add '2m' to each side of the equation.
1ax + -2m + 2m = -12m + 2m

Combine like terms: -2m + 2m = 0
1ax + 0 = -12m + 2m
1ax = -12m + 2m

Combine like terms: -12m + 2m = -10m
1ax = -10m

Divide each side by '1x'.
a = -10mx-1

Simplifying
a = -10mx-1

See similar equations:

| 3.5q-5.9-2.6q=-0.1-3.6 | | 3x^1/4=15 | | 6(t+3)-5t=1 | | -1=D-12 | | 5z+1/5=2z-3/2 | | 6(t+3)-5=1 | | (u+1)(u-6)= | | 5(18-x)=9(4x-32) | | 6.1x-3+x-1.2= | | 12-2X+3X=-3-2 | | -2=1+C | | spx-7=2px+2 | | 2=B-6 | | 4927=n/15 | | .6666y+4=2x | | 3=-11+A | | m-9m-m+9= | | y-36=-28 | | 5/x+8/3x^2 | | 3xy+3yx= | | mx+25=-36 | | f=73905/15 | | 3xy=3yx | | m+7m-3m+4= | | X^2-8=3 | | 73905=n/15 | | V=3.14R2h/3 | | -3/2(1) | | -2-2w+2=2-7w+2 | | m-2m-8m+7= | | 0=-2x^2+6x | | (2xy)(5xy)= |

Equations solver categories